En todas as mans - Toucedo, Diana; Román, Alberte (Trespés Coop. Galega, 2015)
An epic story of determination, of the will to improve the land we inhabit. Two territories: Galicia and Portugal. One reality: communal or uncultivated woodland. In Everyone's Hands introduces viewers to the inhabitants of these areas as they pursue a goal: for these communal territories to generate economic, environmental and social wealth for their villages. The documentary investigates a reality that is as common as it is unknown. A millenary, unique reality, which must also look towards the future.--